Keefektifan Pembelajaran Berbasis Etnomatematika Permainan Tradisional Engklek pada Materi Bangun Datar di Sekolah Dasar - Diah Ruri Handayani; Umi Hanik (Media Pendidikan Matematika, 2026)
This study aims to analyze the effectiveness of learning using ethnomathematics-based instructional media developed through the modification of the traditional engklek game in teaching plane geometry at SD Negeri 1 Gondanglor, Lamongan Regency. This study employed a quantitative approach with a descriptive research design. The subjects of this study were ten second-grade students of SD Negeri 1 Gondanglor in the 2024/2025 academic year. Data were collected through questionnaires, observation sheets, and learning achievement tests. The results showed that: (1) students’ responses to the learning process obtained an average percentage score of 97%, which was categorized as very positive; (2) students’ learning activities were categorized as ideal because the allocation of learning time remained within the effectiveness tolerance limit of approximately 10%; (3) the teacher’s ability to manage the learning process obtained a final score of 96.6, which was categorized as very good; and (4) learning outcomes indicated that 90% of the students achieved the learning objectives with at least a good category. Based on these findings, it can be concluded that learning using ethnomathematics-based instructional media through the modification of the traditional engklek game in teaching plane geometry at SD Negeri 1 Gondanglor, Lamongan Regency can be considered effective because it fulfills four indicators of learning effectiveness, namely students’ responses, students’ learning activities, the teacher’s ability to manage the learning process, and the achievement of learning outcomes